2007
DOI: 10.1021/bi7008823
|View full text |Cite
|
Sign up to set email alerts
|

Human SWI/SNF Drives Sequence-Directed Repositioning of Nucleosomes on C-myc Promoter DNA Minicircles

Abstract: The human SWI/SNF (hSWI/SNF) ATP-dependent chromatin remodeling complex is a tumor suppressor and essential transcriptional coregulator. SWI/SNF complexes have been shown to alter nucleosome positions, and this activity is likely to be important for their functions. However, previous studies have largely been unable to determine the extent to which DNA sequence might control nucleosome repositioning by SWI/SNF complexes. Here, we employ a minicircle remodeling approach to provide the first evidence that hSWI/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 58 publications
4
29
1
Order By: Relevance
“…The 5S NPS was also of particular interest here because of recent studies showing that both WICH components (WSTF and SNF2h) are associated with human 5S genes and that shRNA knock down of WSTF decreases 5S transcript levels (19). Here, as was also seen in prior studies by us and others, we found that the 5S NPS is characterized by a cluster of overlapping individual nucleosome positions (Figure 5B, black bars for nucleosomes with centers between 100 and 140 bp) that give rise to a broad peak of nucleosome coverage over the transcription start site located at position 141 [Figure 5A, black lines (27,28,46)]. This is likely to be because the same DNA properties that result in a single high affinity 146 bp sequence (e.g.…”
Section: Resultssupporting
confidence: 88%
“…The 5S NPS was also of particular interest here because of recent studies showing that both WICH components (WSTF and SNF2h) are associated with human 5S genes and that shRNA knock down of WSTF decreases 5S transcript levels (19). Here, as was also seen in prior studies by us and others, we found that the 5S NPS is characterized by a cluster of overlapping individual nucleosome positions (Figure 5B, black bars for nucleosomes with centers between 100 and 140 bp) that give rise to a broad peak of nucleosome coverage over the transcription start site located at position 141 [Figure 5A, black lines (27,28,46)]. This is likely to be because the same DNA properties that result in a single high affinity 146 bp sequence (e.g.…”
Section: Resultssupporting
confidence: 88%
“…DNA sequence and conformation have been shown to be relevant for remodelling activity [50,58–61]. In particular, nucleosome positioning by the ACF complex can be directed by a defined DNA sequence element that displays high intrinsic curvature [50].…”
Section: Iswi Chromatin Remodellers In Living Cellsmentioning
confidence: 99%
“…To get around end effects entirely, a second recent study examined human SWI/SNF remodeling on three different circular mononucleosome templates [87]. Strikingly, the results showed that hSWI/SNF moves nucleosomes away from initially favored sequences/NPSes, such that, at effective equilibrium, these sequences become the least well occupied areas of the template.…”
Section: Sequence-directed Repositioning By Chromatin Remodeling Compmentioning
confidence: 99%